Love: the agenda for uniting The Muslim Ummah (LUMU) - Syaidatun Nazirah Abu Zahrin,; Rafizah Mohamad Ali, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The power of love and the spirit of love associated with the miracle word “love” can make a great contribution and impact to humanity and the world at large. This paper explores the need and the desire to read the translation of the holy Quran and the total implementation of the wisdom and teachings, the life history of the beloved Prophet Muhammad SAW peace be upon him, so as to know and to love Allah SWT and Ummah. The Prophet Muhammad SAW lifestyle were outlined so that the deeds (amal) can, through the spirit of love unite the Muslim Ummah. For the sake of humanity and the Muslim Ummah such as in educational and economical aspects, we outlined the deeds of LUMU (Love: United Muslim Ummah), may in the course of time, space and the blessings of Allah SWT and our constant remembrance to Rasulullah SAW, Muslim Ummah should be united as long as we are guided by Al Quran and The Sunnah Rasulullah SAW. The ultimate objective of this study is to propose a framework to unite the Muslim Ummah, not only by the power of love, but more so by understanding the concept of love in Islam and build the spirit of love to humanity and Muslims in particular and so shall be appreciative towards the needs of Muslim.